Antifeedant and Repellent Effects of Extracts of Three Plants from Córdoba (Argentina) Against Sitophilus oryzae (L.) (Coleoptera: Curculionidae) - Viglianco, Adriana; Novo, Ricardo; Cragnnolini, Clara; Nassetta, Mirta; Cavallo, Alicia (BioAssay, 2009)
Plant extracts in ethanol, chloroform and hexane of three widely distributed plants in the province of Córdoba were evaluated for their repellency and feeding deterrency to Sitophilus oryzae (L.). The plant species studied were, Aloysia polystachia (Griseb) Moldenke (Verbenaceae); Solanum argentinum Bitter et Lillo (Solanaceae) and Tillandsia recurvata (L.) L. (Bromeliaceae). Antifeedant potential of these extracts was determined by the deterrence or antifeedant test using wheat wafer disks. The Total Coefficient of Deterrence (T) was determined for each extract. Repellency tests were performed using filter-paper circles cut in halves. The extracts were applied on each half at a concentration of 0.31 mg.cm-2. Percentual Repellency (PR) was determined for each extract. The chloroform extracts of A. polystachia had the strongest antifeedant effect (class ++++) followed by the ethanol extracts (class ++++) and hexane extracts of the same species (class +++). Extracts of A. polystachia had stronger antifeedant effect than S. argentinum and T. recurvata extracts. A moderate repellent effect of S. argentinum and A. polystachia extracts on S. oryzae was observed; the hexane extract of S. argentinum was the one with strongest repellency (class 4). Among the extracts analyzed, the strongest antifeedant effect occur with the chloroform extract of A. polystachia and the hexane extract of S. argentinum showed the strongest repellency effect.